Determining ADCC Activity of Antibody‐Based Therapeutic Molecules using Two Bioluminescent Reporter‐Based Bioassays. Issue 11 (17th November 2021) - Garvin, Denise; Stecha, Pete; Gilden, Julia; Wang, Jun; Grailer, Jamison; Hartnett, Jim; Fan, Frank; Cong, Mei; Cheng, Zhijie Jey
Abstract: Antibody Fc effector function is one of the main mechanisms of action (MoA) for therapeutic monoclonal antibodies. Measurement of antibody‐dependent cellular cytotoxicity (ADCC) is critical for understanding the Fc effector function during monoclonal antibody development. This article covers two cell‐based ADCC bioassays which can quantitatively measure the antibody potency in ADCC. Basic Protocol 1 describes the ADCC reporter bioassay using engineered ADCC effector cells which measures the FcγRIIIa‐mediated luciferase reporter activation upon the binding of antibody‐coated target cells. Basic Protocol 2 describes the PBMC ADCC bioassay using primary peripheral blood mononuclear cells (PBMC) as effector cells and engineered HiBiT target cells in an assay that measures the release of HiBiT from target cells upon antibody‐mediated target lysis. Optimization of several key assay parameters including cell handling, effector:target (E:T) ratios, assay plate, and plate reader requirement, and how these parameters impact assay performance are discussed. © 2021 Promega Corporation. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : ADCC reporter bioassay using engineered ADCC bioassay effector cells Basic Protocol 2 : PBMC ADCC bioassay using primary PBMC and engineered HiBiT target cells